2020
DOI: 10.1038/s41418-020-0512-5
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of pathway analysis and pattern recognition predicts sensitization to latest generation TRAIL therapeutics by IAP antagonism

Abstract: Second generation TRAIL-based therapeutics, combined with sensitising co-treatments, have recently entered clinical trials. However, reliable response predictors for optimal patient selection are not yet available. Here, we demonstrate that a novel and translationally relevant hexavalent TRAIL receptor agonist, IZI1551, in combination with Birinapant, a clinically tested IAP antagonist, efficiently induces cell death in various melanoma models, and that responsiveness can be predicted by combining pathway anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Recently, the expression patterns of the regulators involved in TRAIL pathway were used to develop a list of 11 markers that can predict, with 80-100% accuracy, the sensitivity of a melanoma cancer cell towards a combined therapy with TRAIL-R agonist and IAP antagonist. [256]. Thus, a successful future therapy comprises a combination of TRAIL signaling activator with strategies to prevent induction of resistance.…”
Section: Accepted Articlementioning
confidence: 99%
“…Recently, the expression patterns of the regulators involved in TRAIL pathway were used to develop a list of 11 markers that can predict, with 80-100% accuracy, the sensitivity of a melanoma cancer cell towards a combined therapy with TRAIL-R agonist and IAP antagonist. [256]. Thus, a successful future therapy comprises a combination of TRAIL signaling activator with strategies to prevent induction of resistance.…”
Section: Accepted Articlementioning
confidence: 99%
“…Beyond GBM, the CNS is also a frequent secondary site for many cancer metastases, including lung cancer, breast cancer and melanoma, consequently leading to lower treatment responses and poor patient outcomes [50,51]. Therefore, a CNS-targeted therapeutic variant of TRAIL, which shows broad anti-cancer efficacy in various cancer types [15,16,52,53] would be of considerable clinical interest as an anti-cancer agent. Furthermore, recent studies have suggested that endogenous TRAIL plays an important role in immune modulation in multiple sclerosis [54], suggesting a CNS-targeted TRAIL variant could also be used in the treatment of multiple sclerosis and other inflammatory CNS disorders [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Fc-scTRAIL is a second-generation TRAIL-receptor agonist, produced by fusion of a singlechain TRAIL (scTRAIL) trimer to the Fc region of an IgG, resulting in an overall hexavalent TRAIL-receptor agonist that potently engages TRAIL receptor-mediated apoptosis in a wide range of cancer cells [12][13][14][15][16]. The penetration of large biologics, such as TRAIL, into the CNS, is generally prevented by the presence of the blood-brain barrier (BBB), with approximately 0.1% of injected antibody doses reaching the brain parenchyma [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…CellTrace CFSE Cell Proliferation Kit (C34554) was purchased from Thermo Fisher Scientific. FaDu, BT-474, HCT116, HT1080, WM1791c and MCF-7 cells were obtained from different sources and cultured as described previously 36 , 68 70 . LIM1215 were obtained from Merck KGaA (10092301-1VL), SW-620 cells and MDA-MB-231 cells were obtained from CLS Cell Lines Service GmbH (300466), respectively, and cultured in RPMI-1640 (Thermo Fisher Scientific, 11875), 10% FBS (Pan Biotech, P30-3309).…”
Section: Methodsmentioning
confidence: 99%